The Identification of the Biomarkers of Sheng-Ji Hua-Yu Formula Treated Diabetic Wound Healing Using Modular Pharmacology - Jiang, Jing-Si; Zhang, Ying; Luo, Ying; Ru, Yi; Luo, Yue; Fei, Xiao-Ya; Song, Jian-Kun; Ding, Xiao-Jie; Zhang, Zhan; Yang, Dan; Yin, Shuang-Yi; Zhang, Hui-Ping; et al. (Frontiers in Pharmacology, 2021)
Sheng-ji Hua-yu (SJHY) formula has been proved to reduce the severity of diabetic wound healing without significant adverse events in our previous clinical trials. However, based on multi-target characteristics, the regulatory network among herbs, ingredients, and hub genes remains to be elucidated. The current study aims to identify biomarkers of SJHY formula for the treatment of diabetic wound healing. Firstly, a network of components-targets for SJHY formula was constructed using network pharmacology. Secondly, the ClusterONE algorithm was used to build a modular network and identify hub genes along with kernel pathways. Thirdly, we verified the kernel targets by molecular docking to select hub genes. In addition, the biomarkers of SJHY formula were validated by animal experiments in diabetic wound healing mice model. The results validated that the SJHY formula downregulated the mRNA expression of Cxcr4, Oprd1, and Htr2a, while upregulated Adrb2, Drd, Drd4, and Hrh1. Besides, the SJHY formula upregulated the kernel pathways, neuroactive ligand-receptor interaction, and cAMP signaling pathway in the skin tissue homogenate of the diabetic wound healing mice model. In summary, this study identified the potential targets and kernel pathways, providing additional evidences for the clinical application of SJHY formula for the treatment of diabetic wound healing.